Analisis Kesalahan Berbahasa Bidang Morfologi Pada Karangan Narasi Siswa Kelas XI SMA Negeri 6 Palembang - Dinda Luthfiah; Yessi Fitriani; Puspa Indah Utami (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This research aims to describe the forms of linguistic errors in the field of morphology in students' narrative essays, especially prefixes, confixes, suffixes and infixes. The subjects of this research were class XI students of SMA Negeri 6 Palembang. The data taken and researched were three narrative essays. The method used in this research is a qualitative description method. After the data is collected, the results of the analysis are described in writing. The analysis technique used is the test technique. Providing tests that are carried out when students are asked to write narrative essays in the form of short stories related to life experiences regarding family, friends, environmental conditions, etc. The results of this research show that three short stories were analyzed, it was found that all short stories had errors in the use of morphemes.